Differential Role for Transcription Factor Oct4 Nucleocytoplasmic Dynamics in Somatic Cell Reprogramming and Self-renewal of Embryonic Stem Cells - Oka, Masahiro (American Society for Biochemistry and Molecular Biology, 2013)
Oct4 is a member of the POU family of transcription factors and plays a critical role in both maintenance of the undifferentiated state of embryonic stem (ES) cells and in the reprogramming of somatic cells to induced pluripotent stem cells. Oct4 is imported into the nucleus where it functions as a transcription factor; however, the spatiotemporal dynamic behavior of Oct4 remains largely unknown. In the present study we show that Oct4 is a nucleocytoplasmic shuttling protein. Furthermore, although Oct4 mutants with altered nuclear import/export activity were able to maintain the self-renewal of ES cells, they displayed limited potential for cellular reprogramming. These results indicate that the intracellular localization of Oct4, which is dependent on nucleocytoplasmic shuttling, must be more strictly regulated for cellular reprogramming, suggesting that Oct4 plays differential roles in the self-renewal of ES cells and in somatic cell reprogramming.